Two new species of hairy crabs (Pilumnidae) and the first record of Crinitocinus alcocki (Borradaile, 1900) (Acidopsidae) (Crustacea: Brachyura) from Taiwan - Ng, Peter K.l.; Lin, Chia-Wei (Zootaxa, 2023)
Two new species of pilumnid crabs, Heteropilumnus planus n. sp. and Pseudolitochira taiwang n. sp., are described from reefs in Taiwan. Heteropilumnus planus n. sp. is most similar to H. hirsutior (Lanchester, 1900) from Singapore and Japan, but can easily be distinguished by its distinctly flatter carapace, different anterolateral carapace armature, longer ambulatory legs, and male first gonopod structure. Pseudolitochira taiwang n. sp. is most similar to P. crinita Ng & Clark, 2022, from Papua New Guinea but can easily be separated by its carapace physiognomy, armature of the anterolateral carapace margin and proportionately shorter ambulatory legs. Heteropilumnus setosus (A. Milne-Edwards, 1873) is also transferred to Pseudolitochira; and compared with P. taiwang n. sp. The rarely reported acidopsid, Crinitocinus alcocki (Borradaile, 1900) is also recorded from Taiwan for the first time, substantially extending its known range northwards.